2008
DOI: 10.1158/1535-7163.mct-08-0107
|View full text |Cite
|
Sign up to set email alerts
|

Significant antitumor activity in vivo following treatment with the microtubule agent ENMD-1198

Abstract: Clinical studies using the microtubule-targeting agent 2-methoxyestradiol (2ME2; Panzem) in cancer patients show that treatment is associated with clinical benefit, including prolonged stable disease, complete and partial responses, and an excellent safety profile. Studies have shown that 2ME2 is metabolized by conjugation at positions 3 and 17 and oxidation at position 17. To define structure-activity relationships for these positions of 2ME2 and to generate metabolically stable analogues with improved anti-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 30 publications
2
63
0
Order By: Relevance
“…ENMD-1198 was 2.5-to 6-fold more potent than 2ME2 at inhibiting human endothelial cell proliferation depending on the concentrations compared and the cell type. These results are consistent with those obtained with the fibroblast cell line MRC-5 (Supplementary Table S1) and those previously reported for another endothelial cell type (human umbilical vascular endothelial cell) and a variety of human cancer cell lines (19). Furthermore, our results show that, in addition to its improved antiproliferative activity, ENMD-1198 also more potently inhibits endothelial cell motility, chemotaxis, and morphogenesis into capillary-like structures.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…ENMD-1198 was 2.5-to 6-fold more potent than 2ME2 at inhibiting human endothelial cell proliferation depending on the concentrations compared and the cell type. These results are consistent with those obtained with the fibroblast cell line MRC-5 (Supplementary Table S1) and those previously reported for another endothelial cell type (human umbilical vascular endothelial cell) and a variety of human cancer cell lines (19). Furthermore, our results show that, in addition to its improved antiproliferative activity, ENMD-1198 also more potently inhibits endothelial cell motility, chemotaxis, and morphogenesis into capillary-like structures.…”
Section: Discussionsupporting
confidence: 92%
“…The most promising of these analogues, ENMD-1198, has been selected as a lead compound and is currently being tested in phase I clinical trials in patients with refractory solid tumors. In preclinical studies, ENMD-1198 retained potent antitumor properties while displaying improved metabolic stability (19). In the present study, we have shown that ENMD-1198 is a potent antivascular agent.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…2-Methoxyestradiol-3,17-O,O-bis-sulphamate (2MEbi-sMATE) was designed with the above concepts in mind and is currently undergoing clinical trials as STX140 [20]. 2MEbisMATE has a positive prolife for anti-cancer and anti-angiogenic activities.…”
Section: Discussionmentioning
confidence: 99%